The identification of needs for development projects, from the perspective of a Local Government of El Salvador - Quijada Bruno, Jennifer (Revista Relaciones Internacionales, 2022)
This article aims to explore the approach to the processes of identification of needs as part of the development interventions carried out by a Local Government of El Salvador; taking as reference premises that advise the use of functional methods or processes relevant to the context of the intervened communities to carrying out a complete needs identification, so that the identified need corresponds to the real situations of the population, thereby, help to generate an appropriate change that contributes to the development of communities.